Resources for the design of CRISPR gene editing experiments. Issue 1 (December 2015) - Graham, Daniel; Root, David
Abstract CRISPR-based approaches have quickly become a favored method to perturb genes to uncover their functions. Here, we review the key considerations in the design of genome editing experiments, and survey the tools and resources currently available to assist users of this technology.